The shape of galaxy dark matter haloes in massive galaxy clusters: insights from strong gravitational lensing. Issue 3 (12th April 2018) - Jauzac, Mathilde; Harvey, David; Massey, Richard
Abstract: We assess how much unused strong lensing information is available in the deep Hubble Space Telescope imaging and Very Large Telescope / Multi Unit Spectroscopic Explorer spectroscopy of the Frontier Field clusters. As a pilot study, we analyse galaxy cluster MACS J0416.1−2403 ( z  = 0.397, M ( R  < 200 kpc) = 1.6 × 10 14  M⊙ ), which has 141 multiple images with spectroscopic redshifts. We find that many additional parameters in a cluster mass model can be constrained, and that adding even small amounts of extra freedom to a model can dramatically improve its figures of merit. We use this information to constrain the distribution of dark matter around cluster member galaxies, simultaneously with the cluster's large-scale mass distribution. We find tentative evidence that some galaxies' dark matter has surprisingly similar ellipticity to their stars (unlike in the field, where it is more spherical), but that its orientation is often misaligned. When non-coincident dark matter and stellar haloes are allowed, the model improves by 35 per cent. This technique may provide a new way to investigate the processes and time-scales on which dark matter is stripped from galaxies as they fall into a massive cluster. Our preliminary conclusions will be made more robust by analysing the remaining five Frontier Field clusters.